2008
DOI: 10.1254/jphs.fm0070087
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Clinical Aspects of Non-neuronal Acetylcholine: Biological and Clinical Significance of Non-canonical Ligands of Epithelial Nicotinic Acetylcholine Receptors

Abstract: Abstract. Mucocutaneous keratinocytes and bronchial epithelial cells express nicotinic acetylcholine receptors (nAChRs). Emerging evidence indicates that nAChRs can be stimulated also by the tobacco-derived nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N'-nitrosonornicotine (NNN) that can induce tumors in laboratory animals. Nitrosamines may disturb the delicate balance between cell proliferation, growth arrest, and apoptosis. A novel paradigm of cell regulation via nAChR has been disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 33 publications
(39 reference statements)
2
93
1
1
Order By: Relevance
“…The subunits have been cloned from neuron-like cells or cDNA libraries obtained from vertebrate brain, but it has recently been shown that some of them are expressed by non-neuronal cell types throughout the body and have various functions. However, the nAChRs expressed in non-neuronal tissues are beyond the scope of this review and interested readers are referred elsewhere [17][18][19][20][21].…”
Section: Structure Of Thenachrmentioning
confidence: 99%
“…The subunits have been cloned from neuron-like cells or cDNA libraries obtained from vertebrate brain, but it has recently been shown that some of them are expressed by non-neuronal cell types throughout the body and have various functions. However, the nAChRs expressed in non-neuronal tissues are beyond the scope of this review and interested readers are referred elsewhere [17][18][19][20][21].…”
Section: Structure Of Thenachrmentioning
confidence: 99%
“…Reflecting their differential expression, Ly6 proteins are used in diverse biological processes. Apart from acting as GPI-linked cell accessory proteins of the immune system, vertebrate Ly6 proteins function in the modulation of nicotinic acetylcholine receptors (Choo et al, 2008;Darvas et al, 2009;Grando, 2008;Levitin et al, 2008;Liu et al, 2009), remodelling of the extracellular matrix during skeletal muscle regeneration (Kafadar et al, 2009), self-renewal of erythroid progenitors (Bresson-Mazet et al, 2008), and lipolytic processing of triglyceride-rich lipoproteins by binding lipoprotein lipase (Beigneux et al, 2009). The presence of a GPI-anchor in Ly6 molecules, a lipid anchor that tethers the proteins on the outer leaflet of the membrane, also suggests that Ly6 proteins can aggregate in lipid rafts to alter the activity of associated proteins (Bamezai, 2004;Halova et al, 2002).…”
Section: Diverse Functions Of Ly6 Proteinsmentioning
confidence: 99%
“…In addition, the biological and clinical significance of epithelial nAChRs is discussed later in this issue (21). ACh synthesis in keratinocytes is catalyzed by ChAT, while its degradation is catalyzed by AChE (20,22,23).…”
Section: -1 Keratinocytesmentioning
confidence: 99%